Pottery Production in Hellenistic Chalkis, Euboea. Preliminary Notes - Chairetakis, Yannis (Journal of Hellenistic Pottery and Material Culture, 2016)
The reference by Strabo (10, 1, 8) that after the victory at Chaeronea in 335 BCE the Macedonians increased the defense walls of Chalkis including Euripus and the hill of Kanethos, gives us a first insight into the size of the city during the Hellenistic period. Heraclides Criticus, who lived in the 3rd century BCE, writes that Chalkis had a wall perimeter of 13 km in length, fortifying a vast total surface area of 70 stadia (On the Cities of Greece 1, 26). The failure of the Romans to occupy Chalkis during 208 BCE, as the city was impregnable, clearly indicates the presence of a strong defensive wall. In addition, the reference by Titus Livius (31, 23, 1–3) that in 200 BCE the Romans occupied a tower in a sparsely populated area of the city, also reveals that the wall enclosed a large area of the Chalkis peninsula.